Cyberbullying and digital ethics: A bibliometric analysis from a communication research perspective - Deska Imanisa; Rully Khairul Anwar; Yunus Winoto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
This study examines the phenomenon of cyberbullying and digital ethics through a bibliometric approach using the Biblioshiny application in the R programming environment. The dataset, sourced from Scopus between 2014 and 2024, comprises 73 scientific articles that were systematically extracted and analyzed. The findings indicate a rising trend in cyberbullying, particularly its impact on adolescent mental health. Furthermore, the study highlights the critical role of digital ethics education and the practice of forgiveness as potential solutions for fostering a positive and supportive digital environment. This research uses bibliometric analysis to evaluate various aspects of the research, including an overview of the dataset, the number of annual publications, average citations per year, and author contributions. It also analyzed journals, countries, and identified key trends and themes in research. This approach provides a comprehensive insight into the development of research related to cyberbullying and digital ethics over a period of time.